2011
DOI: 10.1002/ijc.25973
|View full text |Cite
|
Sign up to set email alerts
|

Parenteral is more efficient than mucosal immunization to induce regression of human papillomavirus‐associated genital tumors

Abstract: Cervical cancer is a public health concern as it represents the second cause of cancer death in women worldwide. High-risk human papillomaviruses (HPV) are the etiologic agents, and HPV E6 and/or E7 oncogene-specific therapeutic vaccines are under development to treat HPV-related lesions in women. Whether the use of mucosal routes of immunization may be preferable for inducing cell-mediated immune responses able to eradicate genital tumors is still debated because of the uniqueness of the female genital mucosa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 50 publications
3
31
1
Order By: Relevance
“…There are numerous reports of the induction of CD8 + T cell responses in the cervicovaginal mucosa after systemic vaccination with non-replicating vectors (7,11,13,46), and we confirmed these observations using our Ad5-MM2 vector in an intramuscular prime/boost regimen. However, this regimen was qualitatively and quantitatively inferior to the Ivag prime/boost immunization regimen.…”
Section: Figure 11supporting
confidence: 86%
See 1 more Smart Citation
“…There are numerous reports of the induction of CD8 + T cell responses in the cervicovaginal mucosa after systemic vaccination with non-replicating vectors (7,11,13,46), and we confirmed these observations using our Ad5-MM2 vector in an intramuscular prime/boost regimen. However, this regimen was qualitatively and quantitatively inferior to the Ivag prime/boost immunization regimen.…”
Section: Figure 11supporting
confidence: 86%
“…Furthermore, several systemic immunization strategies using live viruses, replication-defective viral vectors, or protein antigens and adjuvant have been shown to induce CD8 + T cell responses in the cervicovaginal mucosa in addition to systemic CD8 + T cell responses (11)(12)(13). Nevertheless, T cell trafficking is clearly regulated at the site of induction through the expression of an array of homing molecules such as integrins, addressins, and chemokine receptors (14).…”
Section: Introductionmentioning
confidence: 99%
“…3 Bone marrow-derived dendritic cells (BMDCs) were isolated using bone marrow cells collected from tibias and femurs of female C57BL/6 mice and cultured in the presence of 150 U/mL recombinant granulocyte-macrophagecolony stimulating-factor (R and D Systems). 2 IFN-g ELISPOT assay IFN-g ELISPOT assays were performed as described 45 A or 1 instillation in B), or s.c. E7 vaccine alone (white diamonds) or followed by Ty21a (black squares, 3 doses in A and 1 dose in B). Mouse survival curves are shown for each treatment (A and B).…”
Section: Preparation Of Murine Cellsmentioning
confidence: 99%
“…1 This can be improved by using appropriate vaccine administration routes, allowing targeting of relevant tumor sites through specific mucosal homing or cancer site retention programs. [2][3][4][5] An alternative approach, irrespective of the immunization route, is to enhance T-cell attraction to the tumor site through the local application of selected chemokines 6 or Toll-like receptor (TLR) agonists that are able to modify the expression of selectins, integrins, chemokines, and chemokine receptors. 7,8 Along this line, we recently reported that intravaginal (IVAG) administration of CpG (a TLR-9 agonist) resulted in the accumulation of CD8 T cells co-expressing CCR5 and CXCR3 chemokine receptors and E-selectin ligands (ESL), most probably through CpG-induced expression of CCL5, CXCL9, CXCL10, CXCL11, and/or E-selectin 9 .…”
Section: Introductionmentioning
confidence: 99%
“…169 In contrast, studies conducted by the Nardelli-Haefliger's group showed that parenteral immunization was more effective than mucosal immunization to control the growth of intrauterine tumor. 170 In this model, it is possible that other effectors, such as antibodies, play a role in the tumor rejection, as the phenomenon of compartmentalization is less evident in humoral responses. Furthermore, the intravaginal immunization route is generally less effective in inducing effector T cell responses, which can be related to the low presence of lymphoid structures in the vagina, since the majority of structures are diffuse clusters of immune cells, and also to the hormonal dependence of this route.…”
mentioning
confidence: 99%